Senses and Emotion Experience at Aceh Tsunami Museum - Nazhar, Ryanty Derwentyana (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out how exhibitions in museums that use various senses can evoke the emotions of visitors and provide visitors with a more memorable spatial experience. In 2004 there was a very powerful Tsunami in Aceh. This incident is remembered in one of the museums designed by Ridwan Kamil, located in Aceh. This museum captures the moment Aceh Tsunami and also tries to present these past events as an exhibition area in a simulation room. This simulation room uses a multisensory delivery method involving several senses. This simulation room is known as the Tsunami Alley. The article discusses what feelings are involved in conveying messages from this space, and the spatial and emotional experience visitors feel. The method used is descriptive qualitative, and the object of this research is the Tsunami Alley of Aceh Tsunami Museum. According to the analysis results, sensory and emotional processes are inseparable and support one another. The application of integrated senses in the museum space will further evoke visitors’ emotions and strengthen the message’s memory. The results of this study are expected to be the development of design references regarding the delivery of news and information using multisensory methods to provide an impressive space experience in exhibition halls.